Form, Meaning, and Wisdom of the Sowan Tradition among the Makeang Luar Community in South Halmahera Regency, North Maluku - Nurfani Nurfani; Farida Maricar; Rudi S. Tawari (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study examines the Sowan tradition on Makeang Island, South Halmahera Regency, North Maluku Province. This tradition is often practiced during Ramadan and aims to help children get used to fasting from an early age. The study will address two questions, the first being: what is the form of the Sowan tradition practiced by the Makeang Luar people? This question also serves as a prophetic effort to counter the current trend in local cultures, which is the gradual decline leading to extinction. A comprehensive description of this tradition not only illustrates how its processes and characteristics are carried out but also serves as a means of documentation that can be preserved as the collective memory of the Makeang Luar community. Additionally, it examines how the Makeang Luar people utilize the wisdom inherent in this tradition to educate children's character from an early age. The research employed a qualitative method using an analytical descriptive approach. This approach was selected because it involved participant observation, in-depth interviews, and literature reviews. Utilizing this methodology allowed the study to gather qualitative data, which was systematically presented based on the facts collected from the field. The findings illustrated how the tradition was practiced, the materials required, and the various meanings and wisdom embedded within it. In terms of meaning, the tradition encompasses several connotations, including resilience, integrity, and maturity. Additionally, regarding local wisdom, the Sowan tradition plays a significant role in shaping children's character from an early age. This character is reflected in their obedience in performing religious duties.